DAMPAK AIR LIMBAH INDUSTRI JOSROYO, KARANGANYAR TERHADAP KADAR TEMBAGA (Cu) DALAM AIR DAN PERMUKAAN TANAH SALURAN AIR PUNGKUK - Dwi Priyo Ariyanto; Hery Widijanto (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2008)
The Effect of Industry Waste in Josroyo, Karanganyar to Copper (Cu) Concentration in Water and Top Soil of Pungkuk Ditch. The purpose of this research was to know the effect of industry waste water distance in Jaten – Karanganyar on Cu concentration in the water and soils at Pungkuk Waterworks, also to know Cu concentration on that waterworks. The kind of this research was explorative research. The independent variable was treatment of take some water and soils sample at 0 km, 0.5 km and 1 km distance from pollutant source at Pungkuk Waterworks and control. The result showed that distance where farther can because concentration Cu concentration change in the soils were heightening but can because Cu concentration change was descending. The heightening of Cu concentration change in the soils was effect of Cu acumulation in the soils. The descending of Cu in the water because precipitation of water Cu and. The value of water pH was influenced by water EMC value. From sample analysis result showed that there was not dirtied of heavy metal especially Cu (between 0.094 – 0.122 ppm). Keyword: Cuprum, Industry waste